Are local people conservationists? Analysis of transition dynamics from agroforests to monoculture plantations in Indonesia - Feintrenie, L.; Schwarze, S.; Levang, P. (2010)
Cash crops are developing in the once forested areas of Indonesia in parallel with market and economic improvements. Perennial crops such as coffee, cocoa, and rubber were first planted in estates by private or public companies. Local people then integrated these crops into their farming systems, often through the planting of agroforests, that is, intercropping the new cash crop with upland rice and food crops. The crop was generally mixed with fruit trees, timber, and other useful plants. A geographic specialization occurred, driven by biophysical constraints and market opportunities, with expansion of cocoa in Sulawesi, coffee in Lampung, and natural rubber in eastern Sumatra. However, during the past three decades, these agroforests have increasingly been converted into more productive monoculture plantations. A common trajectory can be observed in agricultural landscapes dominated by a perennial cash crop: from ladang to agroforests, and then to monoculture plantations. This process combines agricultural expansion at the expense of natural forests and specialization of the land cover at the expense of biodiversity and wildlife habitats. We determined the main drivers of agricultural expansion and intensification in three regions of Indonesia based on perception surveys and land use profitability analysis. When the national and international contexts clearly influence farmers’ decisions, local people appear very responsive to economic opportunities. They do not hesitate to change their livelihood system if it can increase their income. Their cultural or sentimental attachment to the forest is not sufficient to prevent forest conversion